Aggravation of Ossified Ligamentum Flavum Lesion Is Associated With the Degree of Obesity. Issue 5 (June 2023) - Endo, Tsutomu; Koike, Yoshinao; Hisada, Yuichiro; Fujita, Ryo; Suzuki, Ryota; Tanaka, Masaru; Tsujimoto, Takeru; Shimamura, Yukitoshi; Hasegawa, Yuichi; Kanayama, Masahiro; Yamada, Katsuhisa; Iwata, Akira; et al.
Study Design: Retrospective cross-sectional study. Objectives: There is insufficient data on the clinical features of ossification of the ligamentum flavum (OLF) of the thoracic spine and the risk of progression of ossified lesions. The link between obesity and ossification of the posterior longitudinal ligament (OPLL), which frequently coexists with OLF, has been demonstrated. However, the link between obesity and OLF has not been recognized. We aimed to determine the prevalence of obesity in thoracic OLF and whether the severity of OLF is associated with the degree of obesity. Methods: A total of 204 symptomatic Japanese subjects with thoracic OLF and 136 subjects without spinal ligament ossification as controls were included. OLF subjects were divided into 3 groups: 1) localized OLF (OLF <2-intervertebral regions); 2) multilevel OLF (OLF ≥3-intervertebral regions); and 3) OLF + OPLL. The severity of OLF was quantified using the OLF index using computed tomography imaging of the entire spine. Results: The proportion of severely obese subjects (BMI ≥ 30 kg/m 2 ) was significantly higher both in the multilevel OLF group (25.5%) and the OLF + OPLL group (44.3%) than in the localized OLF group (3.6%) and the control group (1.4%) ( P < 0.01). BMI, age, and coexistence of cervical OPLL and lumbar OLF were associated with thoracic OLF index in the multiple regression analysis. Conclusions: Our findings demonstrated that obesity is a distinct feature of multilevel OLF in the thoracic spine and that the severity of OLF is associated with the degree of obesity.